PRAWO RZYMSKIE W POLSCE PRZEDROZBIOROWEJ W ŚWIETLE AKTUALNYCH BADAŃ - Godek, Sławomir (Zeszyty Prawnicze, 2016)
ROMAN LAW IN PRE-PARTITION POLAND IN THE LIGHT OF PRESENT RESEARCH Summary The question of the importance of Roman law in pre-partition Poland has been taxing Polish legal historians for more than two centuries. The achievements to date in this field are significant; however, the issue has not been completely exhausted. In ongoing studies, a number of lines of inquiry have been undertaken that constitute a continuation of earlier investigations, but there are also completely new lines. The great controversy about the role of Roman law in Poland prior to 1795 (viz. the Third Partition) that was initiated by historians in the nineteenth century continues to be of unflagging interest. Research into the Romanisation of the Chronicles of Wincenty Kadłubek is being continued. The attention of researchers is still drawn to the issue of the teaching of Roman law in pre-partition Poland, especially in Kraków, Wilno, and Zamość. Quite significant progress has been made in research on the impact of Roman law on the codification of Poland prior to 1795. Areas of special interest include the Sigismundina, the Lithuanian Statutes and King Stanisław August’s Code. Research on the influence of Roman law on the work of writers who were lawyers in the pre-partition era is less intense than it was in the past. However, there has been a revival in the study of criminal law, as evidenced by the work on crimen laesae maiestatis.